“That’s Just Your Opinion!” - “American Idol” and the Confusion Between Pluralism and Relativism - Ruitenberg, Claudia W. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
Many student-teachers (and the students they teach) fail to understand the difference between opinions in the sense of preferences, and opinions in the sense of judgments. The phrase “That’s just your opinion!” (as wielded by contestants on the television series “American Idol”) is used to shield not only preferences but also judgments from public scrutiny. This misunderstanding springs from confusion between pluralism and relativism. Students’ fear of moral absolutism leads them to espouse relativism when they should be promoting pluralism. Within a conception of education as a social practice that mediates between the private and the public, students must learn both to justify their own judgments and to examine the judgments and justifications that others provide. This requires that students learn to distinguish “just my opinion” and “just your opinion” from morally significant judgments.